Solve for x. 5x + 3(x - 2) = -2(x + 1)

5x + 3(x - 2) = -2(x + 1) 5x + 3x - 6 = -2x - 2 8x - 6 = -2x - 2 8x + 2x = -2 + 6 10x = 4 x = 4/10 x = 2/5

Question

Asked 9/21/2012 12:38:48 PM

Updated 10/6/2017 5:33:13 AM

1 Answer/Comment

Edited by Masamune [10/6/2017 5:27:26 AM]

s

Rating

8

5x + 3(x - 2) = -2(x + 1)

5x + 3x - 6 = -2x - 2

8x - 6 = -2x - 2

8x + 2x = -2 + 6

10x = 4

x = 4/10

x = 2/5

5x + 3x - 6 = -2x - 2

8x - 6 = -2x - 2

8x + 2x = -2 + 6

10x = 4

x = 4/10

x = 2/5

Added 10/6/2017 5:33:13 AM

This answer has been confirmed as correct and helpful.

After he had _____ the tea, he felt better **Weegy:** I need more information to help you. **User:** Use the past participle to complete the sentence.
After he had _____ the tea, he felt better
**Weegy:** begining ....present particle is formed by adding (ing) **User:** After he had _____ the tea, he felt betterdrank
drunk
drunken
drinked
**Weegy:** drunk because you must use the participle form of this verb since it is a past participle tense. (More)

Question

Expert Answered

Asked 9/21/2012 6:42:22 AM

0 Answers/Comments

Simplify.
(-3.9) + (6.01) - (-7.423)
a. -5.513
b. 2.487
c. 9.533 **Weegy:**
(-3.9) + (6.01) - (-7.423)
= 2.11 - (-7.423)
= 2.11 + 7.423
= 9.533
(More)

Question

Updated 10/2/2017 8:25:17 PM

0 Answers/Comments

Evaluate -5x^2 - 3x for x = -2 **Weegy:** (3x-2) squared is 9x^2 - 12x + 4. **User:** If $5,000 is invested at 6% interest, how much money must be invested at 8% interest so that the total interest from the two investments is $660 after one year?
$4,500
$4,000
$5,500 **Weegy:** 400 is 60.60% of 660. (More)

Question

Updated 7/3/2014 11:46:50 PM

1 Answer/Comment

x = -2,

-5x^2 - 3x = -5(-2)^2 - 3(-2) = -20 + 6 = -14

-5x^2 - 3x = -5(-2)^2 - 3(-2) = -20 + 6 = -14

Added 7/3/2014 11:46:50 PM

This answer has been confirmed as correct and helpful.

Find the value of 8 + 2^2 (-3 + 9) ÷ 3. **Weegy:** -6 **User:** Find two consecutive even integers whose sum is 86. Which of the following equations could be used to solve the problem?
4x= 86
2x+ 1 = 86
2x+ 2 = 86
x2+ 2= 86 **Weegy:** 16 (More)

Question

Expert Answered

Updated 5/25/2014 10:41:56 AM

2 Answers/Comments

8 + 2^2 (-3 + 9) ÷ 3

= 8 + 4(6) ÷ 3

= 8 + 24 ÷ 3

= 8 + 8

= 16

= 8 + 4(6) ÷ 3

= 8 + 24 ÷ 3

= 8 + 8

= 16

Added 5/25/2014 10:40:21 AM

This answer has been confirmed as correct and helpful.

Two consecutive even integers whose sum is 86:

x+x+2=86

2x+2=86

2x=86-2

2x=84

x=84/2

x=42

x+2=44

The two consecutive even integers whose sum is 86 are 42 and 44.

x+x+2=86

2x+2=86

2x=86-2

2x=84

x=84/2

x=42

x+2=44

The two consecutive even integers whose sum is 86 are 42 and 44.

Added 5/25/2014 10:41:54 AM

This answer has been confirmed as correct and helpful.

34,619,094

questions answered

There are no comments.